DETERMINATION OF CHARACTERISTIC TIME SCALES IN SEMI-REGULAR STARS: COMPARISON OF DIFFERENT METHODS - Andronov, I. L.; Chinarova, L. L. (Одеські астрономічні публікації, 2017)
Results of the analysis of the characteristic time scales using the periodogram, scalegram and the wavelet analysis are compared for 173 stars most actively observed by the members of the AFOEV and VSOLJ. The periodogram analysis is more effective for stars with stable nearly coherent pulsations, whereas the wavelet analysis is a better tools for stars with switching pulsational modes, e.g. AF Cyg. The scalegram analysis is effective for non-harmonic and chaotic-like variations. The diagrams of the effective time scales obtained using these methods are analyzed for making additional classification of the stars within subclasses. The use of the test functions for automatic classification is discussed. An example analysis is made for S Aql. Particularly, the ephemeris is determined: Max.JD = 2443578.9(3) + 146.d693(6) · E.